Ellagic acid effects on disease severity, levels of cytokines and T-bet, RORγt, and GATA3 genes expression in multiple sclerosis patients: a multicentral-triple blind randomized clinical trial - Jafari Karegar, Sahar; Aryaeian, Naheed; Hajiluian, Ghazaleh; Suzuki, Katsuhiko; Shidfar, Farzad; Salehi, Masoud; Ashtiani, Bahram Haghi; Farhangnia, Pooya; Delbandi, Ali-Akbar (Frontiers in Nutrition, 2023)
Background: Multiple sclerosis (MS) is a chronic autoimmune disease. Ellagic acid is a natural polyphenol and affects the fate of neurons through its anti-inflammatory and antioxidant properties. The present study aimed to investigate ellagic acid effects on disease severity, the expression of involved genes in the pathogenesis of MS, and the levels of related cytokines. Methods: The present study was a triple-blind clinical trial. Eligible patients were randomly assigned to two groups: Ellagic acid (25 subjects) for 12 weeks, receiving 180 mg of Ellagic acid (Axenic, Australia) and the control group (25 subjects) receiving a placebo, before the main meals. Before and after the study, the data including general information, foods intake, physical activity, anthropometric data, expanded disability status scale (EDSS), general health questionnaire (GHQ) and pain rating index (PRI), fatigue severity scale (FSS) were assessed, as well as serum levels of interferon-gamma (IFNγ), interleukin-17 (IL-17), interleukin-4 (IL-4) and transforming growth factor-beta (TGF-β), nitric-oxide (NO) using enzyme-linked immunoassay (ELISA) method and expression of T-box transcription factor (Tbet), GATA Binding Protein 3 (GATA3), retinoic acid-related orphan receptor-γt (RORγt) and Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) genes were determined using Real-Time Quantitative Reverse Transcription PCR (RT-qPCR) method. Findings: Ellagic acid supplementation led to a reduction in IFNγ, IL-17, NO and increased IL-4 in the ellagic acid group, however in the placebo group no such changes were observed (-24.52±3.79 vs. -0.05±0.02, p<0.01; -5.37±0.92 vs. 2.03±1.03, P<0.01; -18.03±1.02 vs. -0.06±0.05, P<0.01, 14.69±0.47 vs. -0.09±0.14, P<0.01, respectively). Ellagic acid supplementation had no effect on TGF-β in any of the study groups (P>0.05). Also, the Tbet and RORγt genes expression decreased, and the GATA3 gene expression in the group receiving ellagic acid compared to control group significantly increased (0.52±0.29 vs. 1.51±0.18, P<0.01; 0.49±0.18 vs. 1.38±0.14, P<0.01; 1.71±0.39 vs. 0.27±0.10, p<0.01). Also, ellagic acid supplementation led to significant decrease in EDSS, FSS and GHQ scores (P<0.05), and no significant changes observed in PRI score (P>0.05). Conclusion: Ellagic acid supplementation can improve the health status of MS patients by reduction of the inflammatory cytokines and Tbet and RORγt gene expression, and increment of anti-inflammatory cytokines and GATA3 gene expression.